EmpathicCare4All. Study protocol for the development of an educational intervention for medical and interpreting students on empathic communication in interpreter-mediated medical consultations. A study based on the Medical Research Council (MRC) framework phases 0–2. (2018) - Krystallidou, Demi; Salaets, Heidi; Wermuth, Cornelia; Pype, Peter
Highlights: Empathic communication is compromised in interpreter-mediated consultations. Joint training between medical and interpreting students is recommended. Protocol for the development of interprofessional education. Expansion of the interprofessional education to other disciplines requires testing. Abstract: Although empathy is associated with positive health outcomes, doctors do not often express empathy and they fail to sufficiently respond to patients' emotional statements. In linguistically diverse healthcare settings empathic communication is compromised even more. This has received little attention in medical education and even less in interpreter education. This project aims to develop an educational intervention for medical- and interpreting students on empathic communication in interpreter-mediated consultations. We rely on the Medical Research Council (MRC) framework for the development and evaluation of complex interventions (phases 0–2). The project will yield valuable insights into the communicative and interactional processes and resources doctors, patients and professional interpreters use in the expression and management of empathic communication in interpreter-mediated consultations.